2020
DOI: 10.1371/journal.pone.0241659
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia predicted illness severity and recovery in patients with COVID-19: A single-center, retrospective study

Abstract: The outbreak of SARS-CoV-2 began in December 2019 and rapidly became a pandemic. The present study investigated the significance of lymphopenia on disease severity. A total of 115 patients with confirmed COVID-19 from a tertiary hospital in Changsha, China, were enrolled. Clinical, laboratory, treatment and outcome data were gathered and compared between patients with and without lymphopenia. The median age was 42 years (1–75). Fifty-four patients (47.0%) of the 115 patients had lymphopenia on admission. More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 26 publications
13
43
1
1
Order By: Relevance
“…In this study we investigated the role of CD8 + T cells in the natural resistance of macaques to severe COVID-19. The relevance of the results is highlighted by the fact that T cell lymphopenia and T cell dysfunction are associated with severe illness in humans with SARS-CoV-2 infection 1 , 2 , 12 , 5 , 13 . Interestingly, we found that depletion of either CD4 + and CD8 + T cells only slightly prolonged the recovery of macaques from a first infection with SARS-CoV-2 and had little or no impact on recovery from re-infection.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study we investigated the role of CD8 + T cells in the natural resistance of macaques to severe COVID-19. The relevance of the results is highlighted by the fact that T cell lymphopenia and T cell dysfunction are associated with severe illness in humans with SARS-CoV-2 infection 1 , 2 , 12 , 5 , 13 . Interestingly, we found that depletion of either CD4 + and CD8 + T cells only slightly prolonged the recovery of macaques from a first infection with SARS-CoV-2 and had little or no impact on recovery from re-infection.…”
Section: Discussionmentioning
confidence: 91%
“… Severe COVID-19 has been associated with T cell lymphopenia 1 , 2 , but no causal effect of T cell deficiency on disease severity has been established. To investigate the specific role of T cells in recovery from SARS-CoV-2 infections we studied rhesus macaques that were depleted of either CD4 + , CD8 + or both T cell subsets prior to infection.…”
mentioning
confidence: 99%
“…Although limited in our ability to investigate predictive power of lymphopenia, partitioning analyses suggest that low lymphocyte counts associate with poor outcomes. Lymphopenia has been associated with adverse outcome in hospitalized patients with COVID-19 [ 11 , 12 , 13 ]. Here we show that even in patients presenting to the ambulatory setting with apparent mild illness, presence of lymphopenia at this early time point portends a poor prognosis with higher likelihood for subsequent complications and hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, immunosenescence represents a further potential contributor to the insurgence of fatal complications in COVID-19 [ 8 , 62 , 63 ]. Lymphopenia and accumulation of immune cells showing immunophenotypic and functional signs of exhaustion were commonly documented in COVID-19 patients, correlating with age and severity [ 43 , 68 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. This strong resemblance to immunosenescence makes COVID-19 a possible scenario to deepen the knowledge about the molecular basis affecting normal immune cell metabolism/lifespan/turnover and to determine the importance of genetic variants and epigenetic modifications behind the appearance of inflammaging and immunosenescence [ 66 , 85 , 86 , 87 , 88 ].…”
Section: Other Immune Response Genesmentioning
confidence: 99%